Posição dos gotejadores e cobertura do solo com plástico, crescimento radicular, produtividade e qualidade do melão - Pivetta, Carina Rejane (2010)
Surface drip irrigation is widespread for the melon crop. To improve the efficiency of this system subsurface drip irrigation and plastic mulching can be used. These management practices can influence soil moisture, and growth and development of plants and hence fruit yeld and quality of melon. Root system can give good information for the design of the irrigation system, because it is closely related to the volume of soil used by the roots to absorb water and nutrients arising from irrigation. This study aimed to evaluate the influence of the position of emitters and plastic mulching on soil moisture, the final growth of roots and yield and fruit quality of drip irrigated melon plants. The experiment was conducted during the spring/summer of 2008 growing season at the Experimental area of the crop science Department of the University of Évora Portugal. Treatments consisted of surface drip irrigation (with and without plastic mulching) and subsurface drip irrigation (without plastic mulching). Soil moisture was monitored using a portable TDR probe and Watermark tensiometers. Leaf area, dry weight and number of leaves per plant were measured. Harvested fruits were separated into commercial and non-commercial and soluble solids content and the lenght and wieth of fruits were measured. Root growth was quantified in terms of root intensity, measured by a minirhizotron (non-destructive method) and root density (destructive method) measured by manual collection of soil samples over roots with an auger. Results indicated no significant differences among treatments for commercial yeld and for fruit quality parameters and vegetative growth of melon. The yeld of unmarketable fruits was significantly higher with surface drip irrigation without plastic mulching in relation to surface drip irrigation with plastic mulching and subsurface drip irrigation. The root length intensity varied significantly between treatments. Under cover of plastic, the increased intensity of roots tended to expand horizontally into the soil, while burying the emitters provided greater root depth in the soil profile, ie between 0.20 and 0.33 m .